Effectiveness evaluation of Pituranthos tortuosus pneumatic parts against Some microbes cause of urinary tract infections. (مجلة البيان العلمية, 2023)
Medicinal plants are considered one of the experimental methods for treating many diseases caused by microbes, especially after the emergence of strains resistant to antibiotics. Therefore, this study was conducted in laboratory of Faculty of Education / Department of Biology, to test inhibitory efficacy of hot and cold aqueous extracts of Pituranthos tortuosus at a concentration of (100, 200, 300, 400) mg/ml against some species of urinary tract infections pathogens (Escherichia coli, Staphylococcus aureus, Klebsilla sp., Proteus sp., Candida albicans), by a sensitivity test in form of agar well diffusion method, then compared with Ciprofloxacin. The results showed that Pituranthos tortuosus extract has good inhibitory activity against all tested microbes, and its effectiveness increased with increasing concentration, and aqueous extracts showed inhibitory activity superior to Ciprofloxacin for Candida albicans Inhibition at diameter (10.2) and (8.0)mm for hot and cold extracts respectively, and antibiotic at concentration 5ug superior was on aqueous extracts against all bacterial species, E.coli, Klebsilla sp. Was most resistant to extracts and antibiotics, were S.aureus and Proteus sp. the most sensitive to extracts and antibiotics.
Keywords: Pituranthos tortuosus; Urinary tract infections; Ciprofloxacin